Usage of repeatedly heated cooking oil and its relationship to knowledge and practice among nurses - Zainah M,; Norsuriani Azni MY,; Nurul Izzati S,; Prasant P,; Loshiny DJ,; Imran Nabil AAA, (Penerbit Universiti Kebangsaan Malaysia, 2023)
Most Malaysians tend to reuse cooking oil in their cooking, which contributes to many diseases. Since nurses are frontliner in the health sector, health education can be given to patients and increase their awareness on the danger of repeatedly heated cooking oil. This study aimed to investigate the level of knowledge and practices regarding the usage of repeatedly heated cooking oil among nurses. A cross-sectional study was conducted among 298 nurses at Hospital Canselor Tuanku Muhriz in July 2022. The nurses completed a questionnaire consisting of sociodemographic factors, knowledge and practice of the usage of repeatedly heated cooking oil. Among 298 nurses, 6.7% had low, 44.0% had moderate and 49.3% had a high level of knowledge on repeatedly heated cooking oil. Respondents’ education level and preferred criteria of cooking oil had significant association with level of knowledge on the usage of repeatedly heated cooking oil (p<0.05). A total of 52% nurses with good practice while 48% had bad practice. There was significant association between knowledge and practices (p<0.001). However, there was no significant association between monthly gross household income with preferred criteria of cooking oil and practices on usage of repeatedly heated cooking oil (p>0.05). The high knowledge on usage of repeatedly heated cooking oil is important as it affects the practice of usage of cooking oil. Early intervention and home cooking should be encouraged to help in reducing the rising of diseases due to the use of repeatedly heated cooking oil.